Family Labour Out-Migration and Technical Efficiency: A Case of Rice Framers in Tanahun District, Nepal (Economic Journal of Nepal, 2013)
This paper explores the relationship between rural out migration and technical efficiency in rice production applying it to the case of Nepal using detailed survey data obtained from 150 farming households over 3 villages throughout 2012/13 growing season. The study finds mean level of technical efficiency is 78, 68 and 66 percent, respectively, for households with no migrant family members, with international migrants and internal migrants. The efficiency differences are explained significantly by age and education of the household head, livestock holding, participation of family members in agricultural related organization and migration status. Both international and internal migration has negative relation with technical efficiency. Similarly, migration of male member has a negative relation and female member migration has no relation with technical efficiency. The study shows that out-migration does not drive agricultural production enhancements, hence, policies intended to minimize farm labour out-migration and improve agricultural efficiency is of paramount importance.